Design of an Automated Instrument for Washing EPR Sample Tubes - LI Jingxin; TONG Wei; YU Lu; ZHANG Zhitao; PI Li (Chinese Journal of Magnetic Resonance)
Many quartz tubes are used in electron paramagnetic resonance (EPR) experiments. These tubes are long and thin, and difficult to clean. To address the problem, an automated washing instrument for EPR sample tubes is designed. The whole instrument mainly includes a water purification machine, water storage tank, booster pump, air compressor, controller, solenoid valve pipeline, and washing rack. Fully automatic washing and drying of EPR sample tubes is achieved by controlling the solenoid valve and the motor/lifter through a Raspberry Pi computer, relay extension module, and Python Graphical User Interface (GUI) program. The instrument is used to clean EPR sample tubes that had contained solid and viscous liquid. The results demonstrate that the instrument has excellent cleaning performance (no impurity signals under low-temperature conditions of T =2 K) and high efficiency (completing a cleaning and drying cycle within 5 min), showcasing significant practical application value.